(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
The article analyzes the awareness of higher education students majoring in 017 "Physical Culture and Sports" of the bachelor’s and master’s degrees regarding the rules of academic integrity using a Google Forms survey. The purpose of the study is to monitor the results of a survey of bachelor’s and master’s degree students majoring in 017 "Physical Culture and Sports" on the understanding of the concept of "academic integrity". Results of the study. The survey involved 76 students majoring in 017 Physical Culture and Sports: 1st year - 40.8%, 3rd year - 32.9%, 4th year - 15.8%, 6th year - 10.5%. Among the respondents, 86.8% are familiar with the concept of "academic integrity," 6.6% are "not familiar," and 6.6% found it difficult to answer. Research and teaching staff (RTS) are informed about the procedure for maintaining academic integrity - 96.1%; 3.3% do not have this information. The concept of "plagiarism" is familiar and possible risks of violation - 94.7%, "difficult to answer" - 3.9%, 1.3% of students are not familiar with this concept. 76.3% of respondents are aware of the use of software for automatic detection of plagiarism in independent, individual, course, and qualification works at the university; 11.8% do not know; 11.8% find it difficult to answer. To report cases of academic dishonesty to the SPE "YES" - 50%, "NO" - 14.5%, "difficult to answer" - 35.5%. The regulatory and legal documents in higher education institutions on this issue are known to 67.1% of applicants; 17.1% - "NO"; 15.8% found it difficult to answer. Conclusions: We note a high level of awareness of the concept of "academic integrity" among applicants - 98.8%. In general, the respondents have a good understanding of all the consequences of violations and the procedure for maintaining academic integrity while studying at the university. A certain proportion of applicants - 17.1% - are not familiar with the regulations in force in the HEI regarding the principles of academic integrity. These shortcomings will be the subject of consideration during the planned and methodological meetings of the Department of Theory and Methods of Physical Education and Sports.